Crystallization and preliminary x-ray analysis of Parkia Pendula lectin - Lombardi, F. R.; Fontes, M. R.M. [UNESP]; Souza, G. M.O.; Coelho, L. C.B.B.; Arni, R. K.; De Azevedo, W. F. (My University, 1998)
Lectins are proteins important in various biological processes such as infection, cell differentiation and metastasis. The Parkia pendula lectin has been crystallized using the hanging-drop vapour diffusion method. X-ray diffraction data were collected using a Rigaku RU300 rotating anode generator and R-AXIS IV diffratometer. The cell parameters for P. pendula lectin are a=93.7Å, b= 16.1.1 Å, c=80.0Å and space group C222. The maximum resolution was of 2.98Å. These data showed a R sym=12.8%.